Effects of Ti addition and wall thickness on microstructure, hardness, and wear properties of spheroidal graphite cast irons - Kaymak, Ki bra; Tazegi, Yigit; Keyvankli, Ahmet Bugra; Gecu, Ridvan (ELSEVIER SCI LTD, 2024)
Spheroidal graphite cast irons (SGCIs) have been commonly used in automotive and energy sectors where superior mechanical strength and wear resistance are required. This paper investigated the performance of the SGCIs under severe wear conditions as a function of Ti content and cooling rate. SGCIs alloyed with various Ti content (0, 0.1, 0.2, 0.3, and 0.5 wt%) were produced by green sand-casting process in different section sizes (10, 30, and 50 mm). Ball-on-disk type wear equipment with an Al2O3 2 O 3 ball was used to determine the wear rates of the SGCI samples. With increasing Ti content, up to 45% of nodular graphite turned into vermicular graphite, depending on the Ti addition and section sizes. Carbide precipitation was observed in the matrix due to the carbide-forming effect of Ti. The hardness and wear resistance of the SGCIs were improved by adding Ti owing to the combined effects of increasing pearlite and TiC particles precipitated in the matrix. Thinner-wall castings provided a faster cooling rate, which improved hardness and wear resistance. Alloying with 0.5 wt% Ti decreased the wear rates up to 35%.
Keywords: Titanium; Ductile iron; TiC; Wear; Graphite morphology; MECHANICAL-PROPERTIES; TITANIUM ADDITION; RESISTANCE; FEATURES; SIZE; Engineering